Characterization and evaluation of an integrated quality monitoring system for online quality assurance of external beam radiation therapy. (29th November 2016) - Hoffman, David; Chung, Eunah; Hess, Clayton; Stern, Robin; Benedict, Stanley
Abstract: Purpose: The aim of this work was to comprehensively evaluate a new large field ion chamber transmission detector, Integral Quality Monitor (IQM), for online external photon beam verification and quality assurance. The device is designed to be mounted on the linac accessory tray to measure and verify photon energy, field shape, gantry position, and fluence before and during patient treatment. Methods: Our institution evaluated the newly developed ion chamber's effect on photon beam fluence, response to dose, detection of photon fluence modification, and the accuracy of the integrated barometer, thermometer, and inclinometer. The detection of photon fluence modifications was performed by measuring 6 MV with fields of 10 cm × 10 cm and 1 cm × 1 cm "correct" beam, and then altering the beam modifiers to simulate minor and major delivery deviations. The type and magnitude of the deviations selected for evaluation were based on the specifications for photon output and MLC position reported in AAPM Task Group Report 142. Additionally, the change in ion chamber signal caused by a simulated IMRT delivery error is evaluated. Results: The device attenuated 6 MV, 10 MV, and 15 MV photon beams by 5.43 ± 0.02%, 4.60 ± 0.02%, and 4.21 ± 0.03%, respectively. Photon beam profiles were altered with the IQM by < 1.5% in the nonpenumbra regions of the beams. The photon beam profile for a 1 cm × 1 cm 2 fields were unchanged by the presence of the device. The large area ion chamber measurements were reproducible on the same day with a 0.14% standard deviation and stable over 4 weeks with a 0.47% SD. The ion chamber's dose–response was linear (R 2 = 0.99999). The integrated thermometer agreed to a calibrated thermometer to within 1.0 ± 0.7°C. The integrated barometer agreed to a mercury barometer to within 2.3 ± 0.4 mmHg. The integrated inclinometer gantry angle measurement agreed with the spirit level at 0 and 180 degrees within 0.03 ± 0.01 degrees and 0.27 ± 0.03 at 90 and 270 degrees. For the collimator angle measurement, the IQM inclinometer agreed with a plum‐bob within 0.3 ± 0.2 degrees. The simulated IMRT error increased the ion chamber signal by a factor of 11–238 times the baseline measurement for each segment. Conclusions: The device signal was dependent on variations in MU delivered, field position, single MLC leaf position, and nominal photon energy for both the 1 cm × 1 cm and 10 cm × 10 cm fields. This detector has demonstrated utility repeated photon beam measurement, including in IMRT and small field applications.